Comorbid pain and migraine chronicity: The Chronic Migraine Epidemiology and Outcomes Study - Scher, Ann I. (Neurology, 2017)
OBJECTIVE: To identify patterns of noncephalic pain comorbidity in people with episodic migraine (EM; <15 headache-days per month) and chronic migraine (CM; ≥15 headache-days per month) and to examine whether the presence of noncephalic pain is an indicator for the 3-month onset or persistence of CM. METHODS: Data from the Chronic Migraine Epidemiology and Outcomes (CaMEO) Study, a prospective, web-based study with cross-sectional modules embedded in a longitudinal design, were analyzed at baseline and the 3-month follow-up. Relationships between the number of noncephalic pain sites and 3-month onset of CM or persistent CM were assessed. RESULTS: Of 8,908 eligible respondents, 8,139 (91.4%) had EM and 769 (8.6%) had CM at baseline. At 3 months, the incidence of CM among those with baseline EM was 3.4%. When adjusted for demographics and headache-day frequency, the odds of CM onset among those with baseline EM increased by 30% (95% confidence interval [CI] 1.21–1.40, p < 0.001) for each additional noncephalic pain site at baseline. Among those with CM at baseline, 50.1% had persistent CM at the 3-month follow-up. After adjustment for demographics, individuals with CM were 15% (95% CI 1.07–1.25, p < 0.001) more likely to have persistent CM for each additional noncephalic pain site at baseline. CONCLUSIONS: These results suggest that noncephalic pain may be a marker for headache chronicity that could be used to identify people with EM at risk of the onset of CM and people with CM at risk of persistent CM.